دماغی موت اور لائف سپورٹ: اسلامی قانونی غور و فکر: BRAIN DEATH AND LIFE SUPPORT ISLAMIC LEGAL CONSIDERATIONS (Al-Aasar, 2025)
The issue of brain death and life support has become an important medical and ethical topic, specially in the context of Islam. This article will provide a detailed analysis of various Islamic scholars' views on the concept of brain death and the use of life support. It will explore whether brain death is considered the end of human life in Islamic jurisprudence, examining the opinions of scholars from different schools of thought. The article will also include the fatwas of various scholars regarding the use of life support. Islamic legal perspectives, medical standards, and ethical questions will be addressed, with definitions of death based on the Quran, Hadith, and medical views. The article will then discuss the definition of brain death and the removal of life support duraing brain death in detail. The goal of this research is to present a clear and comprehensive position on brain death within the framework of Islamic jurisprudence, so as to raise awareness and understanding of this important issue in Muslim society